COINFECTION OF NEWCASTLE DISEASE AND CAPILLARIA SPP. IN LOCAL CHICKENS IN KERTA VILLAGE, PAYANGAN DISTRICT, GIANYAR REGENCY, BALI - Ketut Nanda Maharanthi; Ida Bagus Kade Suardana; I Putu Cahyadi Putra; Ni Wayan Helpina Widyasanti; Ida Bagus Oka Winaya (Buletin Veteriner Udayana, 2025)
Newcastle Disease (ND) is a viral infection that significantly affects poultry and leads to substantial economic losses in the poultry industry. This case study aimed to achieve a definitive diagnosis of the disease in a seven-month-old free-range chicken owned by a resident of Kerta Village, Payangan Subdistrict, Gianyar Regency, Bali. The methodologies employed encompassed the collection of clinical and epidemiological data through history taking, anatomical pathology examination, histopathology, bacteriology, parasitology, and virus isolation via culture of embryonated chicken eggs, which were subsequently confirmed using hemagglutination (HA) and hemagglutination inhibition (HI) tests. Tracing and history-taking revealed that the chicken rearing system was semi-intensive. The chicken population comprised 15 chickens, of which 12 exhibited illness and 10 succumbed within eight days. The clinical signs observed included lethargy, pale bluish drooping wattle and cockscomb, periorbital edema, respiratory distress, reduced appetite and water intake, greenish diarrhea, torticollis, and limp drooping wings. Epidemiological data indicate a morbidity rate of 80%, a mortality rate of 67%, and a case fatality rate of 83%. Anatomical pathological examination through necropsy revealed multiorgan hemorrhage, pulmonary hemorrhage, petechiae in the proventriculus, and intestinal hemorrhage. Organ samples were collected for histopathological analysis with hematoxylin-eosin (HE) staining, which revealed inflammation in various organs, predominantly characterized by lymphocyte infiltration. The HA test demonstrated a high viral titer (29), and the HI test confirmed a positive ND virus infection. Bacteriological examination revealed Escherichia coli in the small intestine and cecum as part of the normal flora. Fecal examination revealed 100 eggs per gram of Capillaria spp. Based on these results, the chickens were diagnosed with a coinfection of Newcastle Disease virus and Capillaria spp. The implementation of routine vaccination programs, improved management practices, and control of poultry movement is recommended as disease prevention measures.